2015
DOI: 10.1371/journal.pone.0118811
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Early Differential Diagnosis of Plateau Iris and Pupillary Block Using A-Scan Ultrasonography

Abstract: PurposeTo distinguish the frequently misdiagnosed plateau iris eyes from pupillary block group and normal group, we compared the ocular biometrical parameters of them by A-scan ultrasongraphy.MethodsIn total, we retrospectively reviewed general characteristics and ocular findings including ocular biometric measurements of 71 normal, 39 plateau iris, and 83 pupillary block eyes.ResultsThe normal controls, plateau iris group and pupillary block group were significantly different in age, but not in gender. The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
3
1
Order By: Relevance
“…As the lens thickens with age, the anterior chamber may become more shallow, thereby leading to a more complex clinical presentation [ 17 , 19 ]. Overall, our findings corroborate prior studies in demonstrating a greater degree of ACD variability in PL compared to other mechanisms [ 19 , 22 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…As the lens thickens with age, the anterior chamber may become more shallow, thereby leading to a more complex clinical presentation [ 17 , 19 ]. Overall, our findings corroborate prior studies in demonstrating a greater degree of ACD variability in PL compared to other mechanisms [ 19 , 22 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…This result agrees with many UBM and anterior segment optical coherence tomography studies. 7 , 17 , 24 Moghimi et al 22 does not support our result as they found a non-significant CACD difference between PI and pupillary block mechanisms of PACG ( P = 0.12).…”
Section: Discussioncontrasting
confidence: 65%
“…The crystalline lens was significantly thicker in the non-PI group ( P = 0.001). Chen et al 24 used A-scan ultrasonography to compare the ocular characteristics among PI, pupillary block, and normal eyes and found a significant lens thickness difference between PI and pupillary block ( P < 0.001). Contrary to these results, Mizoguchi et al 21 found that there was a non-significant difference in the mean value of ALT between PI and non-PI groups ( P = 0.15), which may be due to different ethnic patients, Japanese subjects, involved in their study.…”
Section: Discussionmentioning
confidence: 99%
“…For PAS that must be mechanically separated, we can adopt a separation method far from the peripheral iris, such as using capsulorhexis forceps to pull the middle and peripheral iris to separate PAS, which may reduce peripheral iris damage and re-PAS recurrence. In addition, according to literature21–24 and our observation, non-pupillary block anatomic factors such as plateau iris, peripheral iris hypertrophy, anterior rotation of the ciliary body, and short AL are all high-risk factors for recurrent PAS after surgery. For peripheral iris hypertrophy and plateau iris, argon laser peripheral iridoplasty can be adopted one month after surgery to contract the peripheral iris stroma and create a space between the anterior iris surface and the trabecular meshwork, which may reduce the possibility of re-PAS.…”
Section: Discussionmentioning
confidence: 63%